Competing for the Market - Competitive Strategy for a Small-and-Medium sized Enterprise in the Barcode Labeling Software Industry - Chew, Sing Khie (2005)
The barcode label printing software industry in the South East Asia region is facing a fierce competition where efforts are concentrated on how markets are divided between competitors rather than how to grow them faster. Majority of competitors are already present in this moderate growth market. As the market becomes more crowded and competitive and less predictable, the importance of clear competitive positioning and strategy is critical. This report looks into the industry scenario and the competitive environment that is faced by the company under study. The purpose of the study aims to identify the competitive position of the company in relation to its competitors. It also explores the strategic options and management implications for the company under study that is also open to a small-and-medium sized company in general. The study includes both primary and secondary researches. The main sources of information were from the Strategic Management module and the concepts of positioning learnt from the Marketing module. Both qualitative and quantitative methodologies were used to collect data throughout the study. Besides, relevant reference materials, books, magazines and company records were used together to complete the dissertation. The primary data were collected by means of surveys through telephone and face-to-face personal interviews. The survey attained a response rate of 45.5% (100 out of 220 total respondents participated). The questionnaires for the survey covered industry attractiveness, competitive environment, industry impact, competitive position, market segment, perceived value and company competence pertaining to the barcode label printing software.